A escrita no contexto escolar: relação entre concepção e desenvolvimento - Gonçalves, Ana Cecilia Teixeira (2007)
The present study is linked to the research line of Discourse and Acquisition of the Postgraduate Program of Letters of the Federal University of Santa Maria. Its object of investigation is the writing, which is comprehended as a way of social production. This research aims to analyze the development of the writing in different school contexts. The theoretical-methodological basis for that is the social-discursive interacionism, as proposed by Bronckart (1999, 2006), in which language as well as writing is perceived as a way of social contextualized action. In that perspective, writing represents a human action, which can be developed in different social contexts by various agents and it is always used with a defined purpose. It is also taken into account Vygotsky s ideas (1988, 1989), basis for the social-discursive interacionism, particularly, the question of mediation and the process of internalization. In relation to the methodological instrument, it is used a didactic procedure called Didactic Sequence (DOLZ, NOVERRAZ and SCHNEUWLY, 2004). It represents a type of work, in which the internalization of different textual typologies is aimed. After the application of this instrument, one can observe that the development of writing occurs in different ways in the contexts analyzed (called as School A and School B). Although the similar audience, these schools present different characteristics concerning writing. As a result of the analyses, the relationship between the conception of writing of the institutions and the way as this object is developed is evinced. Thus, it is possible to verify that the texts obtained through the application of the didactic sequence are suitable to the way writing is comprehended in the different institutions, as they reflect the position of the school concerning language and writing. In this way, the results verify that the analysis of the development of writing in school contexts requires the analysis of the established relationship between the institutions, in this case, School A and School B, with the object, the writing.